Biofuels and implications for agricultural water use: blue impacts of green energy - Fraiture, Charlotte de; Giordano, Mark; Liao, Yongsong (IWA Publishing, 2008)
Rising energy prices, geopolitics and concerns over the impact of greenhouse gas emissions on climate change are increasing the demand for biofuel production. At present biofuel production is estimated at 35 billion liters, accounting only for a small part (,2%) of the 1200 billion liters of annual gasoline consumption worldwide. But the contribution of biofuels to energy supply is expected to grow fast with beneficial impacts including reductions in greenhouse gasses, improved energy security and new income sources for farmers. However, biomass production for energy will also compete with food crops for scarce land and water resources, already a major constraint on agricultural production in many parts of the world. China and India, the world's two largest producers and consumers of many agricultural commodities, already face severe water limitations in agricultural production, yet both have initiated programs to boost biofuel production. This paper explores the land and water implications of increased biofuel production globally and with special focus on these two important countries, using the WATERSIM model. It concludes that, although of lesser concern at the global level, local and regional impact could be substantial. In fact, the strain on water resources would be such in China and India that it is unlikely that policy makers will pursue biofuel options, at least those based on traditional field crops.